Silagem de bagaço de laranja na alimentação de cordeiros: Consumo de nutrientes, desempenho e avaliação econômica - Valença, R. L. [UNESP]; Ferreira, A. C.D.; Santos, A. C.P.; Silva, B. C.D.; Santos, G. R.A.; Lima, J. U.N.; Pereira, M. A. (Cordoba University Press (UCOPress), 2017)
This study aimed to evaluate the effect of mastitis pathogens prevalence and somatic cells count (SCC) on dairy cow milk yield (MY) and composition. Milk samples of Holstein cows (n=1163) with 30.97±10.22 kg·d-1 of milk yield were collected and evaluated. Staphylococcus spp. was the most prevalent pathogen. In general, increased SCC decreased MY and lactose concentration and increased milk crude protein content. Coliforms had different SCC and milk crude protein concentrations relation. SCC and milk lactose content relationships were different for S. aureus and Streptococcus spp. Lactose and crude protein are the most sensitive milk components to SCC variation and this relationship is dependent on pathogen presence.
Orange peel silage in feeding lambs: Nutrient intake, performance and economic evaluation